The difference between Montessori curriculum and Malaysia National Preschool curriculum on development skills of preschool children in Kuala Lumpur - Badiei, Mina; Sulaiman , Tajularipin (Sciencedomain International, 2014)
The concern of this study is to find out if Montessori curriculum for early childhood education has any difference with National Preschool curriculum in Malaysia, in terms of growth skills of preschool children. Research methodology was comparative research design. There were two groups; the first group was preschoolers who were trained with Montessori and second group who were trained using Malaysia National curriculum. In this study, independent variable was the curriculum type in each kindergarten and dependent variable was the developmental skills that divided into four major domains of cognitive, language, social and physical development, evaluated by a rating scale for testing developmental skills. The population of the study was all kindergartens in Kuala Lumpur, which were using Montessori approach and National preschool curriculum. The participants were five to six years old children, purposely chosen from the sample. The results indicated that preschool children in Montessori kindergarten performs better in their cognitive, social, and language skills while there is no significant difference on their physical development. Therefore, general conclusion of the results obtained is that Montessori curriculum makes positive effects on cognitive, language and social skills of preschool children and is more efficient than current preschool education curriculum.